Up-Regulation of p53/miR-628-3p Pathway, a Novel Mechanism of Shikonin on Inhibiting Proliferation and Inducing Apoptosis of A549 and PC-9 Non–Small Cell Lung Cancer Cell Lines - Pan, Jieli; Li, Meiya; Yu, Fenglin; Zhu, Feiye; Wang, Linyan; Ning, Dandan; Hou, Xiaoli; Jiang, Fusheng (Frontiers in Pharmacology, 2021)
Shikonin (SHK) is a pleiotropic agent with remarkable cell growth inhibition activity against various cancer types, especially non-small-cell lung cancer (NSCLC), but its molecular mechanism is still unclear. Our previous study found that miR-628-3p could inhibit the growth of A549 cells and induce its apoptosis. Bioinformatics analysis predicted that miR-628-3p promoter sequence contained p53 binding sites. Considering the regulatory effect of SHK on p53, we speculate that SHK may inhibit the growth and induce apoptosis of NSCLC cells by up-regulating miR-628-3p. CCK8, EdU and RTCA assay confirmed the inhibitory effect of SHK on A549 and PC-9 cells. Meanwhile, qRT-PCR and Western blot showed that SHK could promote the expression of p53 and miR-628-3p in a dose-dependent manner. Overexpression of p53 or miR-628-3p can inhibit the growth and promote apoptosis of A549 and PC-9 cells, while silencing p53 or miR-628-3p has the opposite effect. Dual luciferase reporting assay and ChIP assay further verified the direct interaction between p53 and the promoter of miR-628-3p. Gene knockdown for p53 or miR-628-3p confirmed that SHK inhibits the growth and induces apoptosis of A549 and PC-9 cells at least partly by up regulating p53 / miR-628-3p signaling pathway. Therefore, these novel findings provide an alternative approach to target p53 / miR-628-3p axis and could be used for the development of new treatment strategies for NSCLC.